Consequences of ball milling combined with high-pressure homogenization on structure, physicochemical and rheological properties of citrus fiber. (June 2022) - Jiang, Zhanmei; Mu, Sinan; Ma, Chenglong; Liu, Yue; Ma, Yue; Zhang, Minghan; Li, Hongyu; Liu, Xianqi; Hou, Juncai; Tian, Bo
Abstract: Impacts of ball milling (BM) (4, 6, 8, 10 h) combined with high-pressure homogenization (HPH) (60 and 100 MPa, 4 cycles) on structure, physicochemical and rheological properties of citrus fiber were investigated. Compared with single BM treatment, particle size of combined treatment citrus fiber significantly reduced. Scanning electron microscope (SEM) demonstrated that BM combined with HPH unfolded flaky structure of citrus fiber and caused more pores occurred. Fourier transform infrared spectroscopy analysis (FTIR) indicated that combined treatment increased its hydroxyl. At BM 4 h combined with HPH 100 MPa, water holding capacity (WHC), oil holding capacity (OHC), water swelling capacity (WSC), DPPH, ABTS + -radical scavenging capacity and apparent viscosity of citrus fiber increased by 144.74%, 884.52%, 109.56%, 43.90%, 56.80% and 180.49%, respectively, whereas median particle size (D50 ) decreased by 65.24%, compared with single BM treatment. Therefore, BM combined with HPH was an effective physical treatment to modify citrus fiber, remarkably changing its spatial structure and improving its physicochemical properties and apparent viscosity, thus providing a theoretical basis for food industry to obtain excellent citrus fibers. Graphical abstract: Image 1 Highlights: Citrus fiber was treated by ball milling combined with high-pressure homogenization. Antioxidant capacity of combined-treated citrus fiber significantly increased. Apparent viscosity of citrus fiber treated at 4 h and 100 MPa increased by 180.49%.